Research on Economic Performance of Single Pedal Brake for Pure Electric Vehicles based on CLTC Working Condition - Xiangyang Zhao; Qibin Wu (Jixie chuandong)
The economic performance of single pedal matched regenerative braking system for pure electric vehicle under CLTC condition is studied. Firstly， the differences between the two working conditions of CLTC and NEDC are compared， and a virtual simulation model is built on AVL_CURISE platform based on a certain vehicle， a pure electric vehicle model equipped with a single pedal braking energy recovery control system is established. The economic performance differences between the single pedal system and the original parallel braking regenerative system are compared under different working conditions. The simulation results show that， the single pedal braking system is better than the former parallel braking system， the replacement of NEDC with CLTC have limited impact on driving range.